Loop tubulopathies: Bartter's syndrome - Alexander A. Baranov; Leyla S. Namazova-Baranova; Tatyana V. Sergeeva; Olga V. Chumakova; Svetlana S. Paunova; Nurali Z. Zokirov; Olga V. Komarova; Tea V. Margieva; Vladimir K. Tatochenko; Maya D. Bakradze; Elena N. Tsygina; Olga I. Zrobok; et al. (Union of pediatricians of Russia, 2019)
The authors provide a review of current clinical guidelines regarding medical care provided to children with Bartter's syndrome - impaired renal tubular function (loop of Henle) with the development of hypokalemia, hypochloremia, metabolic alkalosis and hyperreninemic hyperaldosteronism.  The specifics of disease epidemiology, etiology and pathogenesis  are described. The issues of differential diagnosis and treatment based on the principles of evidence are covered.